‘Full’ world versus ‘empty’ world paradigm at the time of globalisation - Farina, A.; Johnson, A.R.; Turner, S.J.; Belgrano, A. (Ecological economics, 2003)
The Mediterranean region is characterised by a high diversity mainly due to the integration between natural (land heterogeneity) and human (stewardship) processes. Cultural landscapes are the results of such coevolutive processes. A better understanding of the mechanisms that have assured along the millennia, the maintenance of biological as well as ecological processes seems of extreme importance for our future survival. In North America, a frontier mentality persists in the cultural mindset and rich biodiversity is associated only with remote areas, reflecting a model of an empty world in which human development is completely isolated from the natural (wild) processes. This vision is in contrast with the full world vision of the Mediterranean dwellings. Plasticity, adaptation to disturbance, and the persisting of biological refugia can be considered the most relevant factors responsible for the Mediterranean dynamics. These factors are rare or impossible to find in the North America context from which the dominance of the economic capital over the natural and cultural ones is a very popular model exported worldwide. In this commentary the full world paradigm is presented as an extension of the concept of resilience and ascendancy to propose a new grammar that incorporates self-organisation of natural and human dominated systems into a process of diffuse globalisation of economics and human behaviour.